A New and Robust Method for In‐situ EPR Electrochemistry. Issue 11 (29th August 2019) - Toybenshlak, Maya; Carmieli, Raanan
Abstract: A new and simple design of electrochemical setup for in‐situ generation of free radicals to be measured using X‐band (9.5 GHz) electron paramagnetic resonance (EPR) spectrometer is described. The cell parts are all from commercially available components and requires no specially made glassware. The EPR performance of the setup is demonstrated by in‐situ electrochemical generation of organic radical cations and radical anions such as quinones, perylene‐diimide, pyrene, flavin, tryptophan and tyrosine through oxidation or reduction in solution. The well‐resolved EPR spectra of the radical products were simulated and analyzed and the hyperfine coupling constants have been assigned for the interactions of the unpaired electron with the various ring protons and the nitrogen nuclei. Abstract :